Peran Guru dalam Meningkatkan Kualitas Pembelajaran Pendidikan Jasmani di SD IT Al-Azhar Galang - Tiara Paramita Purba; Khairun Nisa; Nur Arifa Hasanah; Suyono Suyono (Tarbiatuna: Journal of Islamic Education Studies, 2024)
The role of teachers in improving the quality of physical education learning at SD IT Al-Azhar Galang is very important, including the function as a teacher, guide, motivator, and supervisor who ensures that physical activities run safely and effectively. By using a varied and interesting curriculum, teachers can increase student interest and participation. In addition, providing constructive feedback and teaching sportsmanship values ​​helps in building positive character in students. The quality of physical education at SD IT Al-Azhar Galang is highly dependent on the competence and dedication of teachers in carrying out their roles holistically, which ultimately supports the physical, social, and emotional development of students.